Biobank Participants' Attitudes toward Requiring Understanding for Biobank Consent. Issue 1 (22nd December 2021) - Kasperbauer, T.J.; Halverson, Colin; Garcia, Abigail; Schmidt, Karen K.; Schwartz, Peter H.
ABSTRACT: Biobank participants often do not understand the information they are provided during the informed consent process. Ethicists and other stakeholders have disagreed, however, on the appropriate response to these failures in understanding. This paper describes an attempt to address this issue by conducting knowledge tests with 22 recent biobank enrollees, followed by in‐depth, semistructured interviews about the goal of understanding in biobank consent. The interviews revealed that while biobank enrollees thought the information on the knowledge test was important, they did not think that performance on the test should affect whether individuals are permitted to enroll in a biobank. Three main themes emerged from the interviews: helping others by contributing to research is more important than understanding consent forms, less understanding is required because biobank‐based research is low risk, and only a small amount of information in the consent form is really essential. These perspectives should be considered in discussing the ethics and governance of biobank consent processes.